Congenital cytomegalovirus infection. Issue 12 (December 1984) - Preece, P M; Pearl, K N; Peckham, C S
Abstract : Clinical details of 50 infants with congenital cytomegalovirus infection identified in a prospective study are reported. The mean birthweight, gestational age, and head circumference of children with congenital cytomegalovirus infection were not significantly different from those of controls. Three (6%) had symptoms at birth–two neurological and one pneumonitis. In the first four months of life transient hepatosplenomegaly occurred in two infected children and six suffered interstitial pneumonitis. Three congenitally infected children have major neurological handicaps including spastic quadriplegia, microcephaly, and psychomotor delay, and five (10%), including the one with quadriplegia, have sensorineural deafness which is bilateral in three (6%). Estimates based on these findings suggest that the impact of congenital cytomegalovirus infection is comparable to that of congenital rubella in the era before vaccination. Of the 42 children where the nature of maternal infection was classifiable, congenital infection followed primary maternal infection in 32 (76%) and recurrent infection in 10 (24%). Neurological defects followed exposure to primary maternal infection in all three trimesters of pregnancy and also recurrent maternal infection.